2020
DOI: 10.1016/j.ymgmr.2020.100624
|View full text |Cite
|
Sign up to set email alerts
|

Unmet needs in PKU and the disease impact on the day-to-day lives in Brazil: Results from a survey with 228 patients and their caregivers

Abstract: Background Accumulation of phenylalanine (Phe) due to deficiency in the enzyme phenylalanine hydroxylase (PAH), responsible for the conversion of Phe into tyrosine leads to Phenylketonuria (PKU), a rare autosomal recessive inborn error of metabolism with a mean prevalence of approximately 1:10,000 to 1:15,000 newborns. Physical, neurocognitive and psychiatric symptoms include neurodevelopmental disorder as intellectual disability and autism spectrum disorder. The most common treatments such as low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Six of the included studies were published only as an abstract [ 13 – 19 ], ten studies as a thesis [ 20 – 29 ], and the majority (n = 57) were published as full-text in peer-reviewed journals [ 14 , 28 , 30 – 74 ]. Seven further studies [ 27 , 29 , 75 – 79 ] were published initially as a thesis followed by a full-text publication [ 34 , 43 , 80 – 83 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Six of the included studies were published only as an abstract [ 13 – 19 ], ten studies as a thesis [ 20 – 29 ], and the majority (n = 57) were published as full-text in peer-reviewed journals [ 14 , 28 , 30 – 74 ]. Seven further studies [ 27 , 29 , 75 – 79 ] were published initially as a thesis followed by a full-text publication [ 34 , 43 , 80 – 83 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sixty-four of the 79 included studies reported at least one patient-important outcome at individual or population level, and they are displayed in Table 1 for study characteristics. Regarding study design, 18 were case series [ 22 , 23 , 33 , 34 , 40 – 42 , 45 , 54 , 55 , 58 , 60 , 70 , 84 – 87 ], 47 cross-sectional studies [ 6 , 7 , 13 – 15 , 17 – 21 , 24 , 26 , 29 , 30 , 35 – 39 , 43 , 46 , 47 , 53 , 56 , 59 , 61 , 62 , 67 , 68 , 71 , 73 , 75 – 77 , 79 – 81 , 88 – 91 ], 13 case reports [ 34 , 44 , 48 , 51 , 63 , 64 , 69 , 74 , 84 , 87 , 92 – 94 ], and two cohort studies [ 57 , 95 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Children with RIMDs from both high-income and low- and middle-income countries (LMICs) had unmet needs before the pandemic. 7 - 9 Studies in the past years from mostly high-income countries have shown that the coronavirus disease 2019 (COVID-19) pandemic has negatively influenced the needs of both adults and children with a variety of rare diseases like immune deficiencies, genetic disorders. 10 - 15 Information is urgently needed specifically on the unmet needs of children with RIMDs during the COVID-19 pandemic, particularly in LMICs where the majority of such children reside.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, children with PKU will be guided by parents and later in adolescence and adulthood by self-management. This reduces the risks of cognitive decline in babies and mental and neurological problems in adults [ 11 , 12 ]. However, a low Phe diet during childhood but abandoned later in life can increase the risk of other adverse outcomes, such as depression, anxiety and executive functioning deficits in adulthood [ 13 ].…”
Section: Introductionmentioning
confidence: 99%